2021
DOI: 10.1038/s41598-021-94011-z
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic identification of a new sarbecovirus from horseshoe bats in Europe

Abstract: The source of the COVID-19 pandemic is unknown, but the natural host of the progenitor sarbecovirus is thought to be Asian horseshoe (rhinolophid) bats. We identified and sequenced a novel sarbecovirus (RhGB01) from a British horseshoe bat, at the western extreme of the rhinolophid range. Our results extend both the geographic and species ranges of sarbecoviruses and suggest their presence throughout the horseshoe bat distribution. Within the spike protein receptor binding domain, but excluding the receptor bi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(69 citation statements)
references
References 58 publications
12
49
0
Order By: Relevance
“…That is why it is important to monitor the prevalence of CoVs in animals already known as hosts for CoVs (e.g., bats, hedgehogs) and other yet unexplored. Such studies have recently identified novel sarbecovirus in a British horseshoe bat, confirming that these viruses are distributed not only in Asian rhinolophids and revealed that the opportunities for emerging zoonoses are persistent and globally threatening 31 . As bats and hedgehogs are phylogenetically closely related and both are insectivorous animals 17 , 32 , future studies on the circulation of CoVs in these species may shed light on the diversity and evolution of merbecoviruses.…”
Section: Discussionmentioning
confidence: 73%
“…That is why it is important to monitor the prevalence of CoVs in animals already known as hosts for CoVs (e.g., bats, hedgehogs) and other yet unexplored. Such studies have recently identified novel sarbecovirus in a British horseshoe bat, confirming that these viruses are distributed not only in Asian rhinolophids and revealed that the opportunities for emerging zoonoses are persistent and globally threatening 31 . As bats and hedgehogs are phylogenetically closely related and both are insectivorous animals 17 , 32 , future studies on the circulation of CoVs in these species may shed light on the diversity and evolution of merbecoviruses.…”
Section: Discussionmentioning
confidence: 73%
“…Given that ACE2 binding is an ancestral sarbecovirus trait with plastic evolutionary potential, unsampled sarbecoviruses lineages probably have the ability to bind to ACE2 and evolve to bind to human ACE2 unless these traits have been specifically lost as occurred in clade 2. To test this idea, we investigated sarbecoviruses reported after the initiation of our study, including viruses from Africa 19 and Europe 32 , 47 and a new RBD lineage represented by RsYN04 from a Rhinolophus stheno bat in Yunnan, China 15 , which branches separately from the four RBD clades previously described (Fig. 4a ).…”
Section: New Sarbecovirus Lineages Bind To Ace2mentioning
confidence: 99%
“…The analysis also revealed that the insertions in some isolates had further changes involving point mutations, deletions, and insertions. Moreover, as shown in Figure 3A, a similar 5’-UTR-derived insertion at the carboxyl-terminus of ORF8 is seen in five Sarbecovirus β-CoVs from what is considered the animal reservoir for SARS-CoV-2, the Rhinolophus (horseshoe) bats residing in Indochina and Southwest China (Temmam et al 2021) all the way to England (Crook et al 2021).…”
Section: Resultsmentioning
confidence: 72%